Internal friction at crack tip of soda-lime silicate glass - Zhenhan Huang; Minoru Tomozawa (Journal of Non-Crystalline Solids: X, 2025)
Oxide glasses exhibit slow crack growth (SCG) behavior in the presence of water vapor. Oxide glasses are generally considered to be perfectly brittle materials exhibiting no plastic deformation at room temperature. The SCG behavior is generally classified into three regions, region I, region II and region III, in the order of increasing crack velocity as a function of increasing stress intensity. In the regions I and II, crack growth rate is affected by water vapor pressure in environment while in the region III, crack growth rate is independent of water vapor pressure. Water was believed to affect mechanical strength through the surface reaction. In recent years, however, it was observed that water enters into glass at the crack. Water entry into a crack tip is expected to modify the glass properties, e.g. lowering elastic modulus with time through internal friction. In this paper, we observed a residual tensile stress at the crack tip of soda-lime silicate glass after crack growth in regions I and II, but not in region III. Furthermore, this residual tensile stress was observed to decrease with time. This behavior is consistent with the internal friction or viscoelasticity of the crack tip, rather than perfectly elastic deformation. This observation indicates a new mechanism of formation of different crack growth regions (Regions I, II and III) in the slow crack glasses of oxide glasses through internal friction of the crack tip.